PHLDA1 Suppresses TLR4-Triggered Proinflammatory Cytokine Production by Interaction With Tollip - Peng, Hui; Wang, Juping; Song, Xuhong; Huang, Jiangni; Hua, Haoming; Wang, Fanlu; Xu, Ziyun; Ma, Jing; Gao, Jie; Zhao, Jing; Nong, Anna; Huang, Dongyang; et al. (Frontiers in Immunology, 2022)
Pleckstrin homology-like domain, family A, member 1 (PHLDA1) has been reported to be expressed in many mammalian tissues and cells. However, the functions and exact mechanisms of PHLDA1 remain unclear. In this study, we found that PHLDA1 expression was significantly altered in macrophages after exposure to lipopolysaccharide (LPS) in vitro, suggesting that PHLDA1 may be involved in the regulation of TLR4 signaling pathway activated by LPS. PHLDA1 attenuated the production of LPS-stimulated proinflammatory cytokines (TNF-α, IL-6 and IL-1β). Further research showed that the phosphorylation levels of some important signal molecules in TLR4/MyD88-mediated MAPK and NF-κB signaling pathways were reduced by PHLDA1, which in turn impaired transcription factors NF-κB and AP1 nuclear translocation and their responsive element activities. Furthermore, we found that PHLDA1 repressed LPS-induced proinflammatory cytokine production via bind to TOLLIP which restrained TLR4 signaling pathway. A mouse model of endotoxemia was established to confirm the above similar results. In brief, our findings demonstrate that PHLDA1 is a negative regulator of LPS-induced proinflammatory cytokine production by TOLLIP, suggesting that PHLDA1 plays an anti-inflammatory role through inhibiting TLR4/MyD88 signaling pathway under the help of TOLLIP. PHLDA1 may be a novel therapeutic target in treating endotoxemia.